2021
DOI: 10.1002/biof.1776
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the tumor microenvironment by curcumin

Abstract: The tumor microenvironment (TME) is made up of several cells and molecules that affect the survival of cancer cells. Indeed, certain (immunosuppressive) cells which promote tumors can promote the growth of tumors by stimulating the proliferation of cancer cells and promoting angiogenesis. During tumor growth, antitumoral immunity includes natural killer cells and CD8+ T cells cannot overcome immunosuppressive responses and cancer cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 154 publications
(158 reference statements)
0
20
0
Order By: Relevance
“…The TME is formed by these components and their complex interaction with one another. The various cellular compartments that make up the TME are able to critically regulate tumorigenesis, which is essential not only to tumor initiation, malignant progression, and metastasis but also to response to therapy [ 34 , 35 ]. In the TME, the majority of host cells that are drawn to and activated are immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…The TME is formed by these components and their complex interaction with one another. The various cellular compartments that make up the TME are able to critically regulate tumorigenesis, which is essential not only to tumor initiation, malignant progression, and metastasis but also to response to therapy [ 34 , 35 ]. In the TME, the majority of host cells that are drawn to and activated are immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, antitumor cells such as NK cells and cytotoxic T lymphocytes (CTLs, mainly CD8+ T cells) can identify and eliminate cancer cells. They play a role in cancer immune monitoring ( 21 23 ). On the other hand, immunosuppressive cells such as regulatory T cells (Tregs), TAMs, and myeloid-derived suppressor cells (MDSCs) protect cancer cells by evading immune surveillance.…”
Section: Timementioning
confidence: 99%
“…On the other hand, immunosuppressive cells such as regulatory T cells (Tregs), TAMs, and myeloid-derived suppressor cells (MDSCs) protect cancer cells by evading immune surveillance. Subsequently, cancer cells can continue to invade, metastasize and induce angiogenesis ( 21 23 ). At the same time, cancer cells can induce, expand and recruit a large number of tumor-promoting myeloid cells to establish a tumor immunosuppressive microenvironment by driving immunosuppression, regulating the generation of immune cell subtypes ( 21 , 22 ).…”
Section: Timementioning
confidence: 99%
“…Curcumin and resveratrol are plant-derived polyphenolic compounds reported to exhibit therapeutic properties, including anti-inflammatory, antioxidant, and anticancer activities. , Curcumin has been shown to inhibit cancer cell proliferation and induced apoptosis in numerous cancer cell types. Similar to curcumin, resveratrol also inhibits carcinogenesis. , Importantly, both curcumin and resveratrol target cancer cells , and particularly impact cancer cells’ mitochondria. , Previous studies reported that curcumin and resveratrol decrease the mitochondrial membrane potential, , impair the activity of some mitochondrial respiratory enzymes, , and trigger mitochondrial outer membrane permeabilization (MOMP). , Interestingly, curcumin and resveratrol have displayed synergistic effects when administered in tandem. , Both curcumin and resveratrol, however, are hydrophobic, thus exhibiting low solubility in aqueous solutions and poor bioavailability which hinder their therapeutic applicability. Efforts toward increasing the therapeutic efficacy of curcumin and resveratrol have been accomplished by different methods, particularly their inclusion in varied delivery systems. , …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Importantly, both curcumin and resveratrol target cancer cells 8,9 and particularly impact cancer cells' mitochondria. 10,11 Previous studies reported that curcumin and resveratrol decrease the mitochondrial membrane potential, 12,13 impair the activity of some mitochondrial respiratory enzymes, 14,15 and trigger mitochondrial outer membrane permeabilization (MOMP). 16,17 Interestingly, curcumin and resveratrol have displayed synergistic effects when administered in tandem.…”
Section: Introductionmentioning
confidence: 99%